Analisis Penggunaan UPS di Ruang Operasi RSUD Siti Fatimah - Mgs. Chaikal Dzaki; Emidiana Emidiana; Yudi Irwansi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The hospital operating room is one of the most crucial facilities in health services, so it requires a stable, reliable, and uninterrupted electricity supply to ensure patient safety and smooth medical procedures. The slightest electrical outage can pose a major risk, given that almost all vital medical equipment in the operating room relies on an electrical power supply. Therefore, the Uninterruptible Power Supply (UPS) system has an important role as a backup solution to ensure the continuity of electrical energy. This study aims to analyze the performance, capacity, and burden of UPS at Siti Fatimah Palembang Hospital using quantitative methods. Data was obtained through direct observation, interviews with technicians, technical documentation, and measurement of current and load power with standard-compliant measuring equipment. The focus of the analysis was directed at the Online Double Conversion type UPS with a capacity of 20 kVA which functions as the main supplier of backup electricity in the three operating rooms. The measurement results show that the total load reaches 8,855.5 VA or equivalent to 44.2% of the total capacity of the UPS. This load comes from 24 units of vital medical equipment, including operating lights, patient monitors, ventilators, anesthesia machines, and electrosurgical devices spread evenly across three operating rooms. With a power factor of 0.92 and a measurement current of 39.8 A, the performance of the UPS is quite efficient and safe to use. This shows that UPS capacity still has spare space to bear additional loads in the event of an increase in the number of medical equipment in the future. The conclusion of this study is that UPS at Siti Fatimah Palembang Hospital is able to work optimally in maintaining the stability of power supply, so that it can ensure the continuity of critical medical services in the operating room.